Harvey E. Goldber. Jewish Passages-Cycles of Jewish Life. California: University of California Press, 2003. p. 379. - Hodara B., Joseph (Estudios de Asia y África, 2005)
Harvey E. Goldber. Jewish Passages-Cycles of Jewish Life. California: University of California Press, 2003. p. 379.